Research: Legal Responsibility in International Armed Conflicts: An Analytical and Critical Study - Mohammed, Goran Aziz (Journal of Legal and Political Studies, 2024)
The post-World War I period witnessed a major development in international law that regulates international responsibility in the ongoing effort to prevent the recurrence of international wars. With an optimistic view, international wars and civil wars were called international conflicts and non-international armed conflicts. The member states of the League of Nations in 1920 and the member states of the United Nations, which was established in 1945, agreed on codified measures and procedures in international law in the context of its historical development since 1920 until today in determining international responsibility for international and non-international parties that caused the outbreak of these armed conflicts. It also determined the cases and conditions of legitimate self-defense. The international legal system included mechanisms for determining compensation for direct and indirect damages suffered by individuals and groups of civilians, and by parties not concerned or participating in these conflicts, through material compensation and moral compensation. The history of international politics in the period after the end of World War I in 1918 until today has not witnessed a fair application in the classification of international and non-international aggressors, and international and non-international parties. The aggressed, and did not witness fair and just procedures and measures to compensate individuals, groups, and even peoples who were exposed to serious material and moral damages despite the existence of legal cover to compensate these affected parties, this research is an academic participation in confirming this fact, and the necessity of not neglecting it, and emphasizing the danger of ignoring the application of all relevant international charters and agreements in compensating the affected, so the research was divided into three sections: The first presented all the concepts related to international and non-international wars and conflicts, the concepts of aggression, self-defense, and the concepts of international responsibility in redressing damages, and the concept of compensation as one of the most important means of redressing damages, and realistic conclusions about compensation operations, and presented verifiable proposals for compensating individuals, groups, and peoples who were exposed to serious damages whose repercussions still exist to this day. Keywords: International responsibility - concepts and application - realistic criticism.